2014
DOI: 10.1080/15298868.2014.955050
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Self-Compassion: The Role of Attachment and Experiences of Parenting in Childhood

Abstract: Much evidence indicates that self-compassion is related to a wide range of positive outcomes, yet remarkably little is known as to the origins of self-compassion. Here we present two studies that investigate the potential origins of individual differences in self-compassion. In Study 1, participants' (N ¼ 329) recall of high parental rejection and overprotection, and low parental warmth in childhood predicted low self-compassion, and this was mediated by attachment anxiety. Attachment avoidance did not mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 36 publications
5
82
0
2
Order By: Relevance
“…In studies of non‐clinical populations, self‐compassion reliably produces negative correlations with anxious attachment, but weaker or non‐significant correlations with avoidant attachment, supporting the theorized role of negative self‐views (Joeng et al, ; Neff & McGehee, ; Pepping, Davis, O'Donovan, & Pal, ; Raque‐Bogdan, Ericson, Jackson, Martin, & Bryan, ; Wei, Liao, Ku, & Shaffer, ). However, in the only clinical population study we identified, low self‐compassion was uniquely predicted by attachment‐related avoidance, supporting social mentalities model (Mackintosh, Power, Schwannauer, et al, ).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In studies of non‐clinical populations, self‐compassion reliably produces negative correlations with anxious attachment, but weaker or non‐significant correlations with avoidant attachment, supporting the theorized role of negative self‐views (Joeng et al, ; Neff & McGehee, ; Pepping, Davis, O'Donovan, & Pal, ; Raque‐Bogdan, Ericson, Jackson, Martin, & Bryan, ; Wei, Liao, Ku, & Shaffer, ). However, in the only clinical population study we identified, low self‐compassion was uniquely predicted by attachment‐related avoidance, supporting social mentalities model (Mackintosh, Power, Schwannauer, et al, ).…”
Section: Introductionmentioning
confidence: 75%
“…Self‐compassion measured by the full‐scale SCS correlates with various ACEs including low early warmth, parental rejection, and abuse (Neff & McGehee, ; Pepping et al, ; Tanaka et al, ; Vettese, Dyer, Li, & Wekerle, ). However, as noted above, use of the SCS full‐scale means that this may just reflect previously established correlations between abuse and self‐criticism (e.g., Sachs‐Ericsson, Verona, Joiner, & Preacher, ).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this developmental perspective, correlational research demonstrates that self‐compassion is significantly linked to attachment, and that self‐compassion is a potential pathway by which attachment influences mental health (Neff & McGehee, ; Raque‐Bogdan, Ericson, Jackson, Martin, & Bryan, ). Adult recollections of parental rejection have been found to predict low self‐compassion (Pepping, Davis, O'Donovan, & Pal, ), while high self‐compassion is associated with recollections of parental warmth in adults (Pepping et al, ), and maternal support and healthy family functioning among adolescents (Neff & McGehee, ). In line with this, childhood maltreatment also predicts low self‐compassion, which in turn has been found to predict psychological difficulties among adolescents and young adults (Tanaka, Wekerle, Schmuck, Paglia‐Boak, & The MAP Research Team, ).…”
Section: Developmental Perspectives Of Self‐compassion and Emotion Rementioning
confidence: 99%
“…Further support of the hypothesis that self‐compassion is a key mechanism underlying the relationship between childhood experiences and psychological health in later life, is provided by findings that self‐compassion mediates the relationship between insecure attachment and general mental health difficulties (Raque‐Bogdan et al, ), as well as the relationships between both maternal support and family functioning and psychological well‐being among adolescents (Neff & McGehee, ). Limited experimental research also attests to a link between self‐compassion and attachment: Pepping et al () found that individuals who participated in an experiment designed to enhance attachment security reported significant increases in self‐compassion relative to a control group who underwent training in interpersonal skills.…”
Section: Developmental Perspectives Of Self‐compassion and Emotion Rementioning
confidence: 99%
“…More specifically, attachment security has been associated with: self‐transcendent values (Mikulincer, Gillath, Sapir‐Lavid et al ., ); volunteering (Erez, Mikulincer, van Ijzendoorn & Kroonenberg, ; Gillath, Shaver, Mikulincer, Nitzberg, Erez & van IJzendoorn, ); donating blood, or caring for the elderly (McKinney, ); helping and cooperating, and more tolerant attitudes toward members of the outgroup (Mikulincer & Shaver, ; Mikulincer, Shaver, Gillath & Nitzberg, ); greater self‐compassion (Pepping, Davis, O'Donovan & Pal, ); and also, a stronger commitment to social, environmental, and global issues (Mikulincer & Shaver, ).…”
Section: Introductionmentioning
confidence: 99%